Credit support for export: Econometric evidence from the Czech Republic - Karel Janda; Eva Michalíková; Jiří Skuhrovec (Charles University in Prague, Institute of Economic Studies (IES), 2012)
The topic of this paper is quite a novel one - it is one of few empirical academic papers dealing with export credit. Moreover, it is the first analysis of this kind which focuses on transition economies. The paper deals with export credit promotion in the Czech Republic. The development and structure of Czech trade and export support is presented first, followed by an econometric analysis of the gravity model of Czech trade. A panel of 160 countries in 1996-2008 is analyzed and two gravity models of exports for the Czech Republic are estimated, the static model by fixed effects (LSDV estimator) and the dynamic model by System GMM. Due to ambiguous conclusions we assume that the behavior of our explanatory variables is not uniform and our data set behaves as a mixture of countries with heterogeneous behavior. This means that traditional techniques of estimation which include all observations into one model do not give significant results. Thus, we use robust techniques of estimation that solve the problem of heterogeneous patterns in data sets. Out of several possibilities we use the Least Trimmed Squares estimator (LTS) with a leverage point. We show that guarantees are a significant factor that influences positively the volume of exports in the Czech Republic. Moreover, there exist more variables that a effect the size of exports in the Czech Republic. Market forces described by GDP, distance, political risk or gross fix capital formation are significant in our econometric model. We find that higher GDP, shorter distance or lower political risk have a positive impact on Czech exports.
Keywords: F14; G28; C23; 330; export; government promotion; gravity model; panel data